2016
DOI: 10.1016/j.stem.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Skin Adipocyte Stem Cell Self-Renewal Is Regulated by a PDGFA/AKT-Signaling Axis

Abstract: Summary Tissue growth and maintenance requires stem cell populations that self-renew, proliferate and differentiate. Maintenance of white adipose tissue (WAT) requires the proliferation and differentiation of adipocyte stem cells (ASCs) to form postmitotic, lipid-filled mature adipocytes. Here, we use the dynamic adipogenic program that occurs during hair growth to uncover an unrecognized regulator of ASC self-renewal and proliferation, Pdgfa, which activates Akt signaling to drive and maintain the adipogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
121
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 69 publications
(111 reference statements)
4
121
0
1
Order By: Relevance
“…The authors discuss two observed effects from the stimulation of PDGFR in adipose progenitors. Our study showed that decreased PDGFRα signaling leads to a loss of ASCs (8), while a prior study showed that an expression of a constitutively active PDGFRα mutant in mesenchymal cells leads to fibrosis (19,20). It is possible that the level of receptor activation might determine whether the biological response will be maintenance of ASCs or induction of fibrosis.…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…The authors discuss two observed effects from the stimulation of PDGFR in adipose progenitors. Our study showed that decreased PDGFRα signaling leads to a loss of ASCs (8), while a prior study showed that an expression of a constitutively active PDGFRα mutant in mesenchymal cells leads to fibrosis (19,20). It is possible that the level of receptor activation might determine whether the biological response will be maintenance of ASCs or induction of fibrosis.…”
mentioning
confidence: 49%
“…The expansion of dWAT during hair growth occurs through activation of adipocyte precursors that have been identified in other tissues as adipocyte stem cells (ASCs) and enlargement of existing mature adipocytes (6,7). Recent work from our group revealed a role for PDGF signaling in maintaining a sub-population of ASCs (8). Some of these findings have been recently discussed by two editorials from Cappellano & Ploner (9) and Dani & Pfeifer (10).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In adulthood, adipocyte turnover occurs at a rate of ∼10% per year (Spalding et al 2008). In rodents, the degree of turnover may be higher, varying from depot to depot (Wang et al 2013;Rivera-Gonzalez et al 2016). A remarkable and unique property of adipose tissue is the tremendous capacity to expand or contract in different physiological settings.…”
Section: Maintenance and Expansion Of Wat In Adultsmentioning
confidence: 99%